Navigating the Diagnostic Maze of Psoriatic Arthritis sine Psoriasis in Primary Care - Wan Ibrahim, Wan Nur Afifah; Draman, Nani; Mohamad, Noraini; Mohd Rosli, Ritzzaleena Rosli (IIUM Medical Journal Malaysia, 2025)
Psoriatic arthritis, a seronegative spondyloarthropathy is an autoimmune inflammatory joint disease. However, the diagnosis is often delayed due to the absence of specific biomarkers and a lack of awareness among primary care providers, who may be unable to recognize the key features of the condition. We present a case of a 30-year-old woman with a 9-month history of lower back pain and multiple joint pain. Despite elevated inflammatory markers like C-reactive protein and erythrocyte sedimentation rate, other initial tests including rheumatoid factor and antinuclear antibody tests were all negative. The appearance of new skin lesions in the 10th month prompted further evaluation and resulted in a diagnosis of psoriatic arthritis. Treatment with Celecoxib and Methotrexate led to significant improvement in her condition. This case underscores the crucial role of primary care providers in the early detection and management of spondyloarthropathy, helping to prevent joint damage and enhance patient outcomes.